UTILIZATION OF UNCONTROLLED BURNT RICE HUSK ASH IN SOIL IMPROVEMENT - Agus Setyo Muntohar (Jurnal Teknik Sipil UK Petra, 2002)
In this research, a series of laboratory tests has been conducted. The tests were carried out individually or in a combination in which the Rice Husk Ash (RHA) content were varied from 7.5, 10, and 12.5 percent, and the lime content from 2, 4, 6, and 10 percent (by the dry weight of soil). All the samples have been remoulded at their optimum moisture content (OMC) and maximum dry density (MDD). The research shows that lime – rice husk ash decreased the swell of expansive soil and improved its strength and bearing capacity.